Cholangiocarcioma in a cat - Lim, May Lyn; Watanabe, M. (Veterinary Association Malaysia, 2016)
A 7-year-old, intact female Domestic Shorthair cat was referred to University Veterinary Hospital (UVH), UPM for diagnostic workup of a hepatomegaly observed on abdominal radiographs. Physical examination revealed no significant findings except for a distended abdomen. Hematology and serum biochemistry findings included a regenerative anaemia, left shift neutrophilia and a 10-fold elevation in gamma-glutamyltranspeptidase (GGT). Abdominal ultrasound revealed heterechoic liver lobes with irregular margins and presence of nodular and cyst-like structures predominantly affecting the left lobes. A mild ascites was also noted. A fine needle aspiration of the liver was performed and cytology results confirmed a cholangiocarcinoma. Generally, the outcome for cholagiocarcinoma is poor and there is limited information regarding the prognosis for patients with cholangiocarcinoma following chemotherapy or surgery.